2023
DOI: 10.1021/acs.biomac.2c01438
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductive and Biocompatible Nanofibrils from the Self-Assembly of Amyloid π-Conjugated Peptides

Abstract: Owing to their capacity to self-assemble into organized nanostructures, amyloid polypeptides can serve as scaffolds for the design of biocompatible semiconductive materials. Herein, symmetric and asymmetric amyloid π-conjugated peptides were prepared through condensation of perylene diimide (PDI) with a natural amyloidogenic sequence derived from the islet amyloid polypeptide. These PDI-bioconjugates assembled into long and linear nanofilaments in aqueous solution, which were characterized by a cross-β-sheet q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 88 publications
(158 reference statements)
0
8
0
Order By: Relevance
“…Further, we assessed the biocompatibility of the peptide amphiphile 1 toward mice fibroblasts L929 cells, and it was found to be biocompatible (Figure S12C). , Since the peptide 1 alone did not exhibit cytotoxicity, we conducted an MTT assay on the L929 mouse fibroblast cell line after forming its CT complex with TCNQ . Though TCNQ alone exhibited much reduced cell viability toward L929 fibroblast cells (Figure S12D), the CT complex exhibited no cytotoxicity to the fibroblast cells over a broad concentration regime as high as 0.64 mM (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Further, we assessed the biocompatibility of the peptide amphiphile 1 toward mice fibroblasts L929 cells, and it was found to be biocompatible (Figure S12C). , Since the peptide 1 alone did not exhibit cytotoxicity, we conducted an MTT assay on the L929 mouse fibroblast cell line after forming its CT complex with TCNQ . Though TCNQ alone exhibited much reduced cell viability toward L929 fibroblast cells (Figure S12D), the CT complex exhibited no cytotoxicity to the fibroblast cells over a broad concentration regime as high as 0.64 mM (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Current–voltage curves exhibited a clear signature of semiconductors, whereas the cellular assays revealed cytocompatibility and potential application in fluorescence microscopy. [ 71 ] Honick et al. used peptide molecules with different sequences DAIA, VEVAA, VEVFA, VEVGG, VEVFG, VEVAG, and DAVG to modulate exciton transport behavior during supramolecular assembly.…”
Section: Assembly Of Peptide‐based Nanostructuresmentioning
confidence: 99%
“…Current-voltage curves exhibited a clear signature of semiconductors, whereas the cellular assays revealed cytocompatibility and potential application in fluorescence microscopy. [71] Honick et al used peptide molecules with different sequences DAIA, VEVAA, VEVFA, VEVGG, VEVFG, VEVAG, and DAVG to modulate exciton transport behavior during supramolecular assembly. These peptides attached to PDI core were selected based on their ability to foster a wide range of excitonic coupling strengths within organized assemblies, as reflected by experimentally measured steady-state absorption and emission spectra.…”
Section: Self-assembly Of Peptide-function Subunit Conjugatesmentioning
confidence: 99%
“…We have previously reported that the self-assembly of the I 10 sequence into immunostimulatory cross-β nanofilaments tolerates the addition of long peptide epitopes 25,26 and of bulky hydrophobic compounds. 29 Herein, by adjusting the stoichiometry of the peptide monomeric building blocks, the relative density of the antigen and the TLR agonist on the nanostructure could be controlled. These multicomponent nanofilaments induced a robust epitope-specific immune response and completely protected immunized mice from a lethal viral inoculation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this context, we harnessed the high capacity of a 10-mer peptide sequence (I 10 ) to self-assemble into intrinsically immunostimulating nanofilaments organized in a quaternary cross-β-sheet architecture to prepare multicomponent vaccines. We have previously reported that the self-assembly of the I 10 sequence into immunostimulatory cross-β nanofilaments tolerates the addition of long peptide epitopes , and of bulky hydrophobic compounds . Herein, by adjusting the stoichiometry of the peptide monomeric building blocks, the relative density of the antigen and the TLR agonist on the nanostructure could be controlled.…”
Section: Introductionmentioning
confidence: 99%